2020
DOI: 10.3389/fneur.2020.00096
|View full text |Cite
|
Sign up to set email alerts
|

Hemichorea Associated With Non-ketotic Hyperglycemia: A Case Report and Literature Review

Abstract: Objective: To explore the clinical manifestation, diagnosis, therapy, and mechanism of hemichorea associated with non-ketotic hyperglycemia (HC-NH) so as to enhance awareness and avoid misdiagnosis or missed diagnosis of the disease. Methods: A case of HC-NH was reported and reviewed in terms of the clinical features, diagnosis and treatment. Results: Hemichorea associated with non-ketotic hyperglycemia is a rare complication of diabetes mellitus, which is commonly seen in elderly women with poorly-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 29 publications
2
33
0
1
Order By: Relevance
“…The features of neuroimaging are the reversible hyperdense and hyperintense lesions limited to the contralateral striatum areas of the affected limbs without edema and mass effect, on CT and T1-weighted sequences magnetic resonance imaging (MRI), respectively (Oh et al, 2002 ). The radiological findings can be variable signals on T2-weighted, diffusion-weighted imaging, and fluid-attenuation inversion recovery sequences of MRI, and no enhancement on an enhanced scan (Chu et al, 2002 ; Oh et al, 2002 ; Zheng et al, 2020 ). Despite the highly significant correlation between CT and MRI findings, the recent study has shown that there is about one-sixth mismatch and incompatibility between CT and MRI results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The features of neuroimaging are the reversible hyperdense and hyperintense lesions limited to the contralateral striatum areas of the affected limbs without edema and mass effect, on CT and T1-weighted sequences magnetic resonance imaging (MRI), respectively (Oh et al, 2002 ). The radiological findings can be variable signals on T2-weighted, diffusion-weighted imaging, and fluid-attenuation inversion recovery sequences of MRI, and no enhancement on an enhanced scan (Chu et al, 2002 ; Oh et al, 2002 ; Zheng et al, 2020 ). Despite the highly significant correlation between CT and MRI findings, the recent study has shown that there is about one-sixth mismatch and incompatibility between CT and MRI results.…”
Section: Discussionmentioning
confidence: 99%
“…Some histological studies have found that the hyperdense striatal lesions were usually characterized by gliosis, selective neuronal loss, and reactive astrocytes rather than the evidence of hemorrhage or infarction within these areas (Shan et al, 1998 ; Lee et al, 2002 ; Cherian et al, 2009 ). Of course, if conditions permit, MRI remains an essential method helpful in not only diagnosis but also judging prognosis (by the value of apparent diffusion coefficient maps) (Chu et al, 2002 ; Zheng et al, 2020 ). Selected other causes of hyperdense/hyperintense striatal region on CT or T1-weighted MRI should be also considered for the initial visit ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus is one of the highest-incidence diseases worldwide, presenting multiple complications in different organs and systems, such as in the nervous system, both peripheral and central. [1][2][3][4][5][6] The case we present is chorea, which is associated with poor metabolic control. 7 It manifests clinically with movement disorders, such as hemichorea or hemiballism.…”
Section: Discussionmentioning
confidence: 99%
“…Hemichorea associated with non-ketotic hyperglycemia (HC-NH) is a rare complication of diabetes mellitus, especially in patients that do not control their diabetes properly. The pathophysiology of this disease is not well known but chorea symptoms resolve with control over the hyperglycemia and resolve while sleeping [ 15 ]. Other causes of hemichorea-hemiballism include ischemic and hemorrhagic strokes, drugs, motor neuron disease, neurodegenerative diseases, and autoimmune disorders [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemichorea can result from pharmacological agents, in this case, both second-generation antipsychotics and methamphetamine are present and are potential contributors to our patient's presentation. In this case report, we describe a non-ketotic hyperglycemic hemichorea-hemiballismus with other potential secondary etiologies also present [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%